CT-guided cement sacroplasty (CSP) as pain therapy in non-dislocated insufficiency fractures - Andresen, Reimer (Eur J Orthop Surg Traumatol, 2017)
INTRODUCTION: In elderly patients with reduced bone quality, insufficiency fractures of the sacrum are relatively common and are typically associated with severe disabling pain. The objective of the present study was to examine the feasibility of cement augmentation by CSP, to determine post-interventional leakages and other complications, and to present the outcome of pain over the course of 18 months. MATERIALS AND METHODS: In 23 patients (20 women and 3 men) with an average age of 81.3 (71–92) years, a total of 41 sacral fractures were detected by MRI, 5 of them unilateral and 18 bilateral. Conservative treatment initially performed over a period of 3 weeks did not bring any satisfactory reduction in the severe disabling pain. The indication for intervention was established after an interdisciplinary case conference. The intervention was performed under intubation anaesthesia. Single-shot antibiotic prophylaxis was given routinely immediately prior to the intervention. Under sterile conditions, a Jamshidi needle was then advanced into the respective fracture zone in the sacrum from dorsal to ventral (short axis) or from lateral to medial transiliac (transiliac axis). After removing the inner needle, a flexible osteotome was inserted through the positioned hollow needle and used to extend the spongious space in the fracture zone and thus prepare a cavity for the cement filling. High-viscosity PMMA cement was then inserted discontinuously with the aid of a pressure gauge under low-dose CT control. Cement leakages were determined in the CT image on the day after the intervention, all cement outside of the cortical boundary being rated as a leakage. Pain was documented on a visual analogue scale (VAS) on the day before the intervention, on the second day, and 6, 12, and 18 months after the intervention. Additionally occurring complications were recorded, and the patients were asked to rate their satisfaction after 6 and 18 months. RESULTS: CSP was technically feasible in all patients. In the control CT scan, sufficient cement distribution and interlocking with vital bone were found along the course of the fracture in the sacrum. An average of 6.0 ± 0.83 ml of cement was inserted per fracture. Leakage was found in 5 of 41 (12.2%) of the fractures treated, although none were symptomatic. The mean pain score on the VAS was 8.8 ± 0.59 before the intervention, a significant pain reduction (p < 0.0005) was seen on the second post-operative day, with an average value of 2.1 ± 0.36, and this was stable at 2.2 ± 0.28 after 6, 2.3 ± 0.31 after 12, and 2.2 ± 0.41 after 18 months. Now that they no longer experienced disabling pain, all of the patients were fully remobilised and discharged back home. A high level of patient satisfaction was found after 6 and 18 months. CONCLUSION: As a minimally invasive procedure, CSP is an effective treatment method for rapid, significant, and sustained pain reduction.